FUNCTIONAL SWIMMING IN THE PATIENTS WITH MEDULAR INJURY (Fiep Bulletin - online, 2013)
The swimming therapy targeted to functional rehabilitation of damaged spinal cord, have the basic premise with to promote health and functional independence of the individual, the reeducating for a life in society, thus improving their selfimage and self-esteem. The purpose of this study is to direct the conduct of swimming therapy in the process of rehabilitation physiotherapeutic and its effect on the quality of life in spinal cord injured patients. The population was composed of five male patients with clinical diagnosis spinal injury (LRM), aged between 18 and 47 years, residents in the city of Cascavel in the state of Parana, and as a tool for assessment and reassessment of the use of a questionnaire quality of life WHOQUOLbref, written by Fleck (1998) covering four areas before and after intervention physiotherapeutic. The results were satisfactory and an improvement in the physical domain of 26%, field behavioral 27.46%, 23.53% and the social sphere psychological field of 10.63%. So can conclude that the Swimming therapy can influence the quality of life of patients with spinal cord injury.
Keywords: Swimming functional; quality of life; injury Medular